Dasatinib cessation after deep molecular response exceeding 2 years and natural killer cell transition during dasatinib consolidation. Issue 1 (29th November 2017) - Kumagai, Takashi; Nakaseko, Chiaki; Nishiwaki, Kaichi; Yoshida, Chikashi; Ohashi, Kazuteru; Takezako, Naoki; Takano, Hina; Kouzai, Yasuji; Murase, Tadashi; Matsue, Kosei; Morita, Satoshi; Sakamoto, Junichi; et al.
Abstract : Tyrosine kinase inhibitors (TKI) improve the prognosis of patients with chronic myelogenous leukemia (CML) by inducing substantial deep molecular responses (DMR); some patients have successfully discontinued TKI therapy after maintaining DMR for ≥1 year. In this cessation study, we investigated the optimal conditions for dasatinib discontinuation in patients who maintained DMR for ≥2 years. This study included 54 patients with CML who were enrolled in a D‐STOP multicenter prospective trial, had achieved DMR, and had discontinued dasatinib after 2‐year consolidation. Peripheral lymphocyte profiles were analyzed by flow cytometry. The estimated 12‐month treatment‐free survival (TFS) was 62.9% (95% confidence interval: 48.5%‐74.2%). During dasatinib consolidation, the percentage of total lymphocytes and numbers of CD3 − CD56 + natural killer (NK) cells, CD16 + CD56 + NK cells and CD56 + CD57 + NK‐large granular lymphocytes (LGL) were significantly higher in patients with molecular relapse after discontinuation but remained unchanged in patients without molecular relapse for >7 months. At the end of consolidation, patients whose total lymphocytes comprised <41% CD3 − CD56 + NK cells, <35% CD16 + CD56 + NK cells, or <27% CD56 + CD57 + NK‐LGL cells had higher TFS relative to other patients (77% vs 18%; P  < .0008; 76% vs 10%; P  < .0001; 84% vs 46%; P  = .0059, respectively). The increase in the number of these NK cells occurred only during dasatinib consolidation. In patients with DMR, dasatinib discontinuation after 2‐year consolidation can lead to high TFS. This outcome depends significantly on a smaller increase in NK cells during dasatinib consolidation. Abstract : A 2‐year dasatinib consolidation after DMR is feasible and associated with a high estimated treatment‐free survival rate (>60%) at 12 months. Furthermore, dasatinib specifically increased NK cells only during consolidation, but not during discontinuation. Additionally, a greater increase in NK cells during dasatinib consolidation correlated negatively with successful discontinuation.